Analisis Cacat Las Incomplete Fusion Dan Retak Memanjang Pada Waterwall Tube Boiler PLTU Paiton Unit 1 - Sahlan, Sahlan (Semesta Teknika, 2015)
Weld defects in the form of "incomplete fusion" and lengthwise (longitudinal) crackswas observed at the boiler tube welding of steam power plants of Paiton Unit 1, row 3, located860 mm above theheader, .Incomplete fusionmay be caused by incorrect use of the the magnitude of current,welding speed, or manipulation or selection of the electrode being used, thatmay lead tounevenfusityand affect generate the cracks along the incomplete fusion region. Incomplete fusion defects in the waterwall tubes welding being visible from the edge of the boundary between the base material and weld region with the presence of indentation or depression in the form of a very deep crater welding. Indentations or hollows, that will be observed more clearly by using an optical microscope with a magnification 1000X, which in the presence of imperfections observed molecular fusion between grain boundaries and inter-molecular crystal. At 1000X magnification ofthe HAZ (heat affected zone) region,transition structure forming brittle fractures was observedÂ